2022
DOI: 10.1021/acs.joc.2c00096
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Reductive Borylation of Enaminones via C(sp2)–N Bond Cleavage

Abstract: The cleavage and transformation of alkenyl C­(sp2)–N bonds is a significant synthetic challenge. Herein we described an unprecedented nickel-catalyzed reductive borylation of enaminones to synthesize β-ketone boronic esters. Notably, B2pin2 played the dual role in this process, and water served as a hydrogen source, which was transferred to target products. The air-stable nickel catalyst was applied to the cleavage of alkenyl C­(sp2)–N bonds, concomitant with the reductive process of the alkenyl boronic ester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Generally, transition metals and their complexes are required as the catalysts. 21 Many transition metal catalysts may be toxic and metal contamination in the products is hard to remove. Therefore, developing transition metal-free methods for C-N bond cleavage is a great challenge, but will attract much attention in the drug and pharmaceutical industry in the future.…”
mentioning
confidence: 99%
“…Generally, transition metals and their complexes are required as the catalysts. 21 Many transition metal catalysts may be toxic and metal contamination in the products is hard to remove. Therefore, developing transition metal-free methods for C-N bond cleavage is a great challenge, but will attract much attention in the drug and pharmaceutical industry in the future.…”
mentioning
confidence: 99%
“…7 Despite the rapid progress achieved in recent years in difluorocarbene-triggered cycloaddition reactions, efficient methods for the synthesis of fluorine-containing monocyclic rings are still rare, and the development of a convenient and practical approach for their construction is desireable, especially in terms of complex multisubstituted fluorine-containing rings. Herein, as part of our ongoing research on the transformation of enaminones, 8 we reported the synthesis of monocyclic 2,2-difluoro-2,3-dihydrofurans with readily accessible enaminones and cost-effective ClCF 2 CO 2 Na as a difluorocarbene precursor (Scheme 2).…”
mentioning
confidence: 99%
“…Very recently, Li and Xu demonstrated that diboron(4)/pyridine cocatalyzed [3 + 2] cycloaddition of cyclopropanes and alkenes . Considering the above challenge on the synthesis of indolizine and our ongoing research on organoboron chemistry and enaminone, it was significant and feasible to construct nitrogen-containing heterocycles via pyridine-boryl radical. Herein, we successfully developed a cascade cyclization/aromatization reaction between enaminone and pyridine for the synthesis of a range of functionalized indolizines (Scheme , III).…”
mentioning
confidence: 99%